Effective approaches to poverty reduction selected cases from the Asian Development Bank. (Economics working papers., 2019)
The case studies highlight effective approaches to poverty reduction by providing broader access to economic opportunities, promoting resilience, and empowering communities through improved governance. Stories about experiences gained from the successful implementation of projects serve as examples of how to develop and adopt better policies and practices toward eradicating poverty.